The role of genetic analysis in correct diagnosis of eosinophilic variant of chromophobe renal cell carcinoma - Molnár, Ágnes; Yusenko, Maria; Kovacs, Gyula; Banyai, Daniel (Anticancer research, 2020)
Background/Aim: It has been suggested that eosinophilic variant of chromophobe renal cell carcinoma (chRCC) with low chromosome number or lack of genomic alteration has an excellent prognosis in comparison to classic chRCC. The aim of our study was to analyse the phenotypical variations of 77 chRCCs, including 7 eosinophilic ones, each diagnosed unequivocally by genetic means. Materials and Methods: DNA isolated from chRCCs was subjected to array comparative genomic hybridisation (CGH) for establishing the chromosome alteration. Original histological slides were evaluated for cellular phenotype and growth pattern and compared to the genetic alterations. Results: Loss of the entire chromosome 1, 2, 6, 10, 13, 17 and 21 occurred in 95%, 94%, 86% 90% 82% 90% and 66% of the cases, respectively. The number of chromosome alterations in eosinophilic forms of chRCC corresponded to those found in classic chRCC with pale-reticular cytoplasm or mixed cellular characteristics. Three of seven eosinophilic variants with loss of 4, 10 and 11 chromosomes showed metastasis at the time of diagnosis whereas only 3 metastatic tumors were noticed among the 70 classic chRCC. We did not find discriminating difference in number of chromosome alteration between classic and eosinophilic forms of chRCC. Conclusion: Eosinophilic chRCC has a more aggressive biology than the classic form. To avoid diagnostic pitfall of eosinophilic renal cell tumors with uncertain diagnosis, a genetic analysis should be carried out.